Validating the Grit-S scale among postgraduate students in a South African distance education institution - Young, Kelly Anne; Archer, Elizabeth (Frontiers in Education, 2023)
Grit has been associated with student success in a plethora of higher education (HE) studies. In order to measure and evaluate the predictive validity of grit in student success in a particular context, an appropriate, reliable and valid instrument is required. This paper examines the short grit scale’s (Grit-S) psychometric properties among a sample of 837 postgraduate students enrolled at the University of South Africa (UNISA). This appears to be the first study to explore the psychometric rigor of the scale among postgraduates within a South African distance education (DE) setting. An exploratory factor analysis (EFA) followed by partial confirmatory factor analysis (PCFA) revealed that the same two factors put forth by Duckworth et al. (2007) could be detected in the items tested (i.e., ‘passion’ and ‘perseverance’ for long-term goals), and in combination explained 57.22% of the variance. Model fit indices for the two-factor solution were satisfactory (NFI = .984; TLI = .981; CFI = .991; RMSEA = .038). Further results from the item analysis indicated that both factors (passion and perseverance) were soundly reliable, as was the overall Grit-S scale, yielding Cronbach Alpha values of ≥ .77. Overall, the study provides promising evidence that the Grit-S scale can validly and reliably be used to operationalize grit (and the separate dimensions of perseverance and passion) among postgraduates pursuing their DE studies. Further theoretical and practical implications are discussed.